Digital Marketing Communication Strategy to Increase Guest Visits at Royal Regantris Kuta - Adeline, Shannon; Senaharjanta, Ignasius Liliek (Indonesian Journal of Social Science Research, 2026)
The digital transformation of the hospitality industry has intensified competition and reshaped consumer decision-making processes. This study examines how digital marketing communication strategies are implemented to optimize guest visits at Royal Regantris Kuta. Using a five-stage consumer decision model consisting of attention, interest, search, action, and share as an analytical framework, this qualitative descriptive research explores how paid, owned, and earned media are strategically coordinated across digital platforms. Data were collected through in-depth interviews with key informants responsible for digital marketing management, supported by documentation and digital platform observation. The findings reveal that the optimization of guest visits is not solely driven by exposure, but by the structured coordination of digital touchpoints that strengthen credibility during the search stage and reduce consumer uncertainty prior to booking decisions. The study demonstrates that effective digital marketing communication in the hospitality sector depends on the alignment between visibility, trust-building mechanisms, and post-purchase engagement. These findings contribute to the contextual application of the five-stage consumer decision model within competitive tourism destinations.